Hubungan Antara Kompetensi Profesional Guru dengan Hasil Belajar Peserta Didik Madrasah Aliyah Subulussalam 2 OKU Timur - Effendi, Effendi; Nuryana, Nila (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2020)
This study aims to determine the relationship between teacher professional competence and students' learning outcomes of Madrasah Aliyah Subulussalam 2 East OKU. The research method used was quantitative causal correlations (cause and effect). The population of the study was all students of Madrasah Aliyah Subulussalam 2 East OKU. Sampling was done by using random method, with a total sample was 30 students. In this study there were two variables: variable (X) was the teacher's professional competence and variable (Y) was the students' learning outcomes. Variable X data was obtained by distributing questionnaires, while Y variable was obtained by multiple choice test questions. The questionnaire data obtained an average value was 87.8 from a maximum score was 101 while the average value of the test was 70.13 from a maximum value was 90. From the data, it was processed by using the Product Moment correlation formula. From the results of data processing, it was obtained that the rxy value was 0.79. While t table was 2.048 at N = 28 with a significant level of 5% and t-obtained was 6.82. This means that t-obtained > t table (6.82> 2,048) Ha is accepted while Ho was rejected. From these data it can be concluded that there is a significant relationship between teacher professional competence and students' learning outcomes of Madrasah Aliyah Subulussalam 2 East OKU.